2001
DOI: 10.1063/1.1337590
|View full text |Cite
|
Sign up to set email alerts
|

Probe diagnostics of electronegative plasmas with bi-Maxwellian electrons

Abstract: A method to detect the parameters of electronegative plasmas with bi-Maxwellian electrons using a Langmuir probe is proposed by applying the test function. The radial model for the positive ion collection is extended and found to be more appropriate for density detection than the orbital motion limited model. The parameters of a diffused Ar/SF6 plasma are obtained by cylindrical and spherical probes for various Ar/SF6 ratios over a pressure range from 0.5 to 10 mTorr. The density ratio of bulk to hot electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…8 Moreover, in the same range of n ni /n e , a recently developed test function method allows the determination of electronegative plasma parameters in the approximations of Maxwellian or bi-Maxwellian electrons. 9,10 For n ni /n e Ͻ5 the decrease in is too small to predict with certainty the negative ion presence. Based on various probe measurements performed in electronegative plasmas, [11][12][13] Amemiya reviewed that even in such a situation the negative ion presence can be proved by the appearance of a double hump structure ͑DHS͒ in the second derivative of the probe current, I p Љ , and that T ni and n ni can be obtained from the hump ͑peak͒ at larger V, where V is the probe bias.…”
Section: Introductionmentioning
confidence: 97%
“…8 Moreover, in the same range of n ni /n e , a recently developed test function method allows the determination of electronegative plasma parameters in the approximations of Maxwellian or bi-Maxwellian electrons. 9,10 For n ni /n e Ͻ5 the decrease in is too small to predict with certainty the negative ion presence. Based on various probe measurements performed in electronegative plasmas, [11][12][13] Amemiya reviewed that even in such a situation the negative ion presence can be proved by the appearance of a double hump structure ͑DHS͒ in the second derivative of the probe current, I p Љ , and that T ni and n ni can be obtained from the hump ͑peak͒ at larger V, where V is the probe bias.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, the modeling of ion collection by a cylindrical probe (e.g., [9,19]) requires the tip radius to be much smaller than the Debye length, which is violated under the present experimental condition. Hence the CP will not be used to obtain the ion density in this study and future PIC simulations, similar to the process reported in Sheridan [12], are need to correct the ion density measured by a cylindrical probe.…”
Section: Introductionmentioning
confidence: 98%
“…10) Owing to the weak bonding of electrons to heavy neutral atoms or molecules among single positive-charged ions and electrons, it is not easy to characterize the negative ions, although there have been various methods to measure them such as optical emission spectroscopy (OES), 11) the laser photodetachment (LPD) method, 2,12,13) the ion acoustic wave (time-of-flight) method (IAW) [15][16][17] and the use of electric probes. 11,14,[17][18][19][20][21][22][23][24][25][26] For conventional methods using electric probes and OES, fully ionized plasma with singly positive-charged ions and a Boltzmann electron with one thermal temperature are assumed. In the LPD method, there is a need to define the cross section of a high-power laser beam, which often ionizes the neutral gas leading to the generation of electrons, which which contaminate the detached electrons purely generated from negative ions.…”
Section: Introductionmentioning
confidence: 99%